2018
DOI: 10.1093/gigascience/giy086
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome and transcriptome maps of the entirely black native Korean chicken breed Yeonsan Ogye

Abstract: Background Yeonsan Ogye (YO), an indigenous Korean chicken breed (Gallus gallus domesticus), has entirely black external features and internal organs. In this study, the draft genome of YO was assembled using a hybrid de novo assembly method that takes advantage of high-depth Illumina short reads (376.6X) and low-depth Pacific Biosciences (PacBio) long reads (9.7X).FindingsThe contig and scaffold NG50s of the hybrid de novo assembly were 362.3 Kbp and 16.8 Mbp, respectively. The completeness (97.6%) of the dra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 66 publications
0
30
0
Order By: Relevance
“…Of the 6900 Ogye lncRNAs that we annotated in our previous study [55], 6565 were expressed with fragments per kilobase of transcript per million mapped reads (FPKM) ≥ 1 in at least one tissue, whereas 13,765 of Ensembl chicken protein-coding genes (release 81; ) were expressed. Tissue-specific genes with a four-fold higher maximum expression value than the mean value over the 20 tissues were depicted in the genome using a Circos plot (Supplementary Figure S1a, green track).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 6900 Ogye lncRNAs that we annotated in our previous study [55], 6565 were expressed with fragments per kilobase of transcript per million mapped reads (FPKM) ≥ 1 in at least one tissue, whereas 13,765 of Ensembl chicken protein-coding genes (release 81; ) were expressed. Tissue-specific genes with a four-fold higher maximum expression value than the mean value over the 20 tissues were depicted in the genome using a Circos plot (Supplementary Figure S1a, green track).…”
Section: Resultsmentioning
confidence: 99%
“…Recent research has shown that the Fm phenotype (associated with the Fm region) is related to domestication and has been intensely artificially selected, with about 1.5-folder blacker level [ 48 ]. A previous study found that an inverted duplication affecting EDN3 , a key gene in dermal melanin located on chromosome 20 in the Fm region, caused excessive accumulation of black pigment in chickens [ 54 , 55 ]. We also detected an inversion at 10.97–11.52 Mb and a duplication at 10.74–12.55 Mb in EDN3 , which overlaps the Fm region.…”
Section: Discussionmentioning
confidence: 99%
“…The C. hongkongensis gills (~20 mg) were homogenized and fixed in 1,000 µl of cold 70% ethanol for 15 min at 4°C. Chicken (Gallus gallus, 1.02 Gb; Sohn et al, 2018) red blood cells (RBCs; standard sample) were used as internal reference to estimate C. hongkongensis DNA content. The fixed gill cells and 10 µl chicken RBCs were mixed and then stained with 0.2 ml of propidium iodide (PI) solution (Solarbio) (100 μg/ml DNase-free RNase A [TakaRa], 500 μg/ ml PI dye in PBS) was added followed by incubation in the dark for 15 min.…”
Section: Genome Size Estimation By Flow Cytometry Analysismentioning
confidence: 99%